Genetic Variation and De Novo Mutations in the Parthenogenetic Caucasian Rock Lizard Darevskia unisexualis - Badaeva, Tatiana N. (Public Library of Science, 2008)

(untitled)
Unisexual all-female lizards of the genus Darevskia that are well adapted to various habitats are known to reproduce normally by true parthenogenesis. Although they consist of unisexual lineages and lack effective genetic recombination, they are characterized by some level of genetic polymorphism. To reveal the mutational contribution to overall genetic variability, the most straightforward and conclusive way is the direct detection of mutation events in pedigree genotyping. Earlier we selected from genomic library of D. unisexualis two polymorphic microsatellite containg loci Du281 and Du215. In this study, these two loci were analyzed to detect possible de novo mutations in 168 parthenogenetic offspring of 49 D. unisexualis mothers and in 147 offspring of 50 D. armeniaca mothers . No mutant alleles were detected in D. armeniaca offspring at both loci, and in D. unisexualis offspring at the Du215 locus. There were a total of seven mutational events in the germ lines of four of the 49 D. unisexualis mothers at the Du281 locus, yielding the mutation rate of 0.1428 events per germ line tissue. Sequencing of the mutant alleles has shown that most mutations occur via deletion or insertion of single microsatellite repeat being identical in all offspring of the family. This indicates that such mutations emerge at the early stages of embryogenesis. In this study we characterized single highly unstable (GATA)(n) containing locus in parthenogenetic lizard species D. unisexualis. Besides, we characterized various types of mutant alleles of this locus found in the D. unisexualis offspring of the first generation. Our data has shown that microsatellite mutations at highly unstable loci can make a significant contribution to population variability of parthenogenetic lizards.